Correlation of gender with neonatal outcome in babies born to mothers with hypertensive disorder of pregnancy - Mathias, Olivia Jean; Vachhani, Simran; Rajan, A. R.; Joshi, Deepak (International Journal of Contemporary Pediatrics, 2026)
Background: Hypertensive disease of pregnancy (HDOP) has a prevalence of 6.9%. The study analysed the correlation between gender and neonatal outcomes in mothers with HDOP. Methods: A retrospective descriptive study analysed 203 neonates born to mothers with HDOP in a tertiary care hospital. Results: During the study period 3259 deliveries were conducted of which 203 deliveries met our inclusion criteria (106 male and 97 female). In 142 neonates (69.95%) mode of delivery was LSCS with male gender being significantly higher (p<0.05). Of 203 neonates, 65 (32.02 %) needed NICU care. Respiratory distress syndrome (61.11%) was the commonest morbidity. The mean period of gestation in male neonates was 262.17 days and 262.29 in females. The mean birth weight for male neonates was 2186.52 grams, while for female neonates was 2507.53 grams (p<0.05). Of the 203 neonates in our study, 93 were found to be small for gestational age. The mean duration of NICU stay for neonates was 5.08 days for males and 1.55 days for females. (p<0.05). The mean duration of hospital stay for male neonates was 13.52 days and for female neonates was 7.74 days (p<0.05). The mean placental weight for the female gender was 386.29 g and for the male gender was 390.69 g. Conclusions: Male gender showed statistically significant positive correlation (p<0.05) for low birth weight, mode of delivery and duration of both NICU and Hospital stay.